AN ANALYSIS OF MORAL VALUES IN DOSTOYEVSKYâ€™ THE BROTHERS KARAMAZOV NOVEL - Ria Saraswati (Jurnal Akrab Juara, 2018)
It is obvious that Literature is an important subject to be studied since it reflects every single aspect of human life. In this article, the researcher investigates moral values where it becomes one of the aspects to be analyzed in Literature where the novel of â€œThe Brothers Karamazovâ€ written by Fyodor Dostoyevsky is chosen by the researcher as the subject of the research with some important considerations. The criteria of moral values used by the researcher is based on the definition of morality in descriptive sense proposed by Gert. In addition, the design of this research is qualitative research since the researcher tries to explore the moral values as reflected in the novel of â€œThe Brothers Karamazovâ€ descriptively. As the result, the researcher finds at least four dimensions exposed in account of morality in term descriptive sense. These are Russian Men, Masters and Serfs, Religious Institution, and Russian Women. Keywords: moral values, the brother karamazov, Fyodor Dostoyevsky.